2002
DOI: 10.2310/6650.2002.33436
|View full text |Cite
|
Sign up to set email alerts
|

Saliva Analysis in the Clinical Setting: Revisiting an Underused Diagnostic Tool

Abstract: We think that saliva analysis is a useful, worthwhile diagnostic tool because saliva collection is noninvasive, easy, and inexpensive and may be performed by the patient with no need for the involvement of medical personnel, if so desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(80 citation statements)
references
References 30 publications
0
73
0
1
Order By: Relevance
“…Salivary enhancement of CS effects might explain the high prevalence of CS-induced OP cancer. In addition, saliva is always considered an efficient protective medium -an antibacterial, antiviral, anticariogenic, antioxidative, mechanical and thermal protector, etc (Nagler et al, 2002b). However, the current study demonstrates that in the 'wrong circumstances' saliva becomes highly deleterious, such as when it is exposed to CS.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Salivary enhancement of CS effects might explain the high prevalence of CS-induced OP cancer. In addition, saliva is always considered an efficient protective medium -an antibacterial, antiviral, anticariogenic, antioxidative, mechanical and thermal protector, etc (Nagler et al, 2002b). However, the current study demonstrates that in the 'wrong circumstances' saliva becomes highly deleterious, such as when it is exposed to CS.…”
Section: Discussionmentioning
confidence: 65%
“…Further significant credence for the mechanism suggested is found in the reported existence of redox metals (iron and copper) in saliva and of their deleterious role in the pathogenesis of the damage inflicted on salivary glands by ionising irradiation (another source of low reactive free radicals) (Nagler et al, 1997;Nagler and Baum, 2003). Finally, major support for the suggested mechanism can be found in a recent report which demonstrated that in humans the Sm/Sl saliva contains much higher concentrations of iron than does the parotid saliva, especially when secreted under resting conditions (Nagler et al, 2002b). This undoubtedly adds to explanation given previously for the profound cytotoxic behavior of Sm/Sl saliva as compared with parotid saliva, as well as for the general role of salivary redox metals, such as iron, in the underlying mechanism of the synergism phenomenon.…”
Section: Discussionmentioning
confidence: 95%
“…However, the results of JIA-related reductions of MMPs 2, 3 and 9 in the saliva are puzzling, as these specific MMPs were found to be increased in the serum and in the synovial fluid of JIA and rheumatoid arthritis (RA) patients (14)(15)(16)(17). It is well established that most enzymes found in the saliva originate from the salivary or oral mucosal cells and not from the serum (28). This could explain an absence of increase in the salivary MMP in JIA, but not a decrease.…”
Section: Discussionmentioning
confidence: 99%
“…These were measured in saliva, which was collected as described earlier (Nagler et al, 2002), shortly before the administration of the definitive curative treatment. This included surgical removal of the primary tongue tumour, neck dissection and, in most cases, post-operative adjuvant radiotherapy.…”
Section: Patients and Study Designmentioning
confidence: 99%